La place des rites dans le quotidien maghrébin à l’exemple de La fille de la Casbah de Leïla Marouane - Cebula, Magdalena (Romanica Silesiana)
In her first novel, La fille de la Casbah (The Daughter of the Casbah), published in 1996, Leïla Marouane describes daily life of women living in the heart of Algiers in the late 80s. This was the time of sociopolitical transformations (the birth of multiparty and the rise of Islamic fundamentalism). This article analyzes the practices and rituals mentioned by the writer on three levels: that of everyday life, tradition and Islam. The analysis demonstrated that these rites are used as benchmarks in the world undergoing violent changes, but at the same time they hinder the emancipation of the modern woman by dictating her behaviors consistent with social roles attributed to her (daughter, wife, mother). Key words: Maghrebian literature, Islam, ritual, tradition